The Success of Fostering Religious Character to Boost the Enthusiasm of New Participants in Education - Ahdar; Ramli, Nurleli; Musyarif; Mustafakama Waeduereh; Ikhwana (TADRIS: Jurnal Pendidikan Islam, 2024)
The phenomenon of society's need to fulfill their children's religious character has an impact on the community's interest in enrolling their children in public schools. As a result, public schools experience a decrease in the number of students. Several public schools in the Ajatappareng Region of South Sulawesi Province implement various strategies for fostering religious character to meet the community's needs. This research aims to describe the strategies undertaken by public schools in shaping the religious character of students to increase the enthusiasm of new students. The study was conducted at SMP Negeri 1 Parepare and SMP Muhammadiyah Boarding School. These two locations were selected because they have successfully increased student enthusiasm through religious character development programs. The research method used is qualitative descriptive with data collection techniques through observation, documentation, and interviews with school officials. The collected data is then analyzed using the Milens data analysis model. The schools use the trans-internalization model to shape the religious character of students by involving all teachers, staff, and parents. The division of responsibilities for character development between schools and parents is clear, as outlined in the student's memorization control book. The formation of students' character adjusts to the religious dimension, resulting in observable changes in student behavior towards improvement in akhlaq (morality). The success of religious character formation has an impact on the increase of new student applicants in the 2023/2024 school year by 100% from the previous year.